Proposal of a method for obtaining an economic dosage for clay-containing mortars - Gomes, Adailton de Oliveira (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper proposes a method of obtaining an optimised, economic dosage for mortars used in wall and ceiling rendering, which was developed at CETA (Mortar Technological Centre) and applies specially to clay-containing mortars used in the RMS — Metropolitan Region of Salvador. It also presents some characteristics and uses of mineral clay as a mortar ingredient. It discusses other methods proposed to dose mortar and supports the use of weight proportions for wall and ceiling rendering mortar, instead of volume proportion, which is traditionally used at construction sites. It presents the basic parameters and procedures used to determine the proportion for mortar containing clay minerals. It determines cement usage based on mortar utilization; it calculates the proportions of mortars according to the amount of fines; and determines water proportion based on clay characteristics. Based on this data, it determines the trace and describes the adjustments after the experimental mixture. Finally, it suggests a method to relate the dry weight of the materials obtained from the weight proportion to the humid volumes measured at construction sites. It presents results of mortar tests containing several types of clays from three different regions dosed by the method proposed on this paper, comparing the values obtained with those from a reference mortar. It also discusses the use of other additions. It concludes by inviting the scientific community to use the proposed method and to contribute to the establishment of an optimised dosage methodology for rendering mortars.